Description of age-related changes in cervical sagittal alignment based on pelvic incidence classification in asymptomatic Chinese population - Wang, Zheng; Hu, Xinli; Cui, Peng; Liu, Xu; Zhu, Weiguo; Kong, Chao; Wang, Wei; Lu, Shibao (European spine journal, 2023)
Purpose To investigate the pelvic incidence (PI)- and age-related cervical alignment changes of Chinese healthy population. Methods Six hundred and twenty-five asymptomatic adult subjects, who underwent the standing whole spinal radiograph, were recruited in this work. The sagittal parameters were measured, including Occipito-C2 angle (O-C2), C2–7 angle (C2–7), cranial arch, caudal arch, T1-slope (T1S), C2–7 sagittal vertical axis (C2–7 SVA), thoracic kyphosis (TK), lumbar lordosis (LL), pelvic tilt (PT), sacral slope (SS), PI, and sagittal vertical axis (SVA). All subjects were stratified into 5 age groups, namely 40–59 years, 60–64 years, 65–69 years, 70–74 years, and 75 years and above, with each age group further divided into 2 subgroups based on PI (deeming PI < 50° as low PI, and PI ≥ 50° as high PI). The correlations between PI or age, and other sagittal parameters were assessed. The age-related changes of sagittal parameters in each PI subgroup were also assessed, followed by one-way analysis of variance analysis for change comparison between age groups. Results The average cervical sagittal parameters were as below: 18.2 ± 6.8° for O-C2, 10.4 ± 10.2° for C2–7, 3.9 ± 7.5° for cranial arch, 6.5 ± 7.1° for caudal arch, 23.6 ± 7.3° for T1S, and 21.0 ± 9.7 mm for C2–7 SVA. There was no obvious difference observed between PI and cervical sagittal parameters, excepting for caudal arch. While, C2–7, cranial arch, caudal arch, T1S, and C2–7 SVA increased remarkably with the age. Thereof, C2–7 exhibited great increases at the age of 60–64 years and 70–74 years, respectively, cranial arch increased notably at 60–64 years of age, and caudal arch developed obviously at 70–74 years of age, regardless of PI. Conclusion This study showed the PI- and age-related cervical alignment changes of Chinese healthy population. Based on the classification in our study, high or low PI apparently did not correlate with the occurrence of cervical degenerative disease.